Effects of oral phosphocysteamine and rectal cysteamine in cystinosis. Issue 12 (December 1991) - van't Hoff, W G; Baker, T; Dalton, R N; Duke, L C; Smith, S P; Chantler, C; Haycock, G B
Abstract : Diurnal variation in leucocyte cystine and the effects of equimolar single doses of oral phosphocysteamine and rectal cysteamine were studied in eight patients with cystinosis, aged 1.8-16.5 years. No significant diurnal variation in leucocyte cystine was found. Absorption of cysteamine was reduced after rectal administration compared with the oral dose: mean (SD) peak concentration 17.2 (6.3) mumol/l v 36.4 (5.5) mumol/l at 40 min and mean (SD) area under the curve 22.3 (14.3) v 59.4 (33.1) mumol/h/l. Oral phosphocysteamine significantly reduced the mean (SD) leucocyte cystine from 8.09 (0.47) to 3.26 (1.48) nmol 1/2 cystine/mg protein at three hours. At 12 hours the mean leucocyte cystine was significantly lower than the pretreatment concentration. Rectal cysteamine did not significantly reduce the mean leucocyte cystine concentration. In conclusion, phosphocysteamine suspension may be administered every 12 hours. Rectal cysteamine administration is feasible but higher doses are required before efficacy can be judged.